The Effect of Organizational Culture And Decision Making Toward Organizational Citizenship Behavior of Teacher in Pre-School - Griet Helena Laihad; Rita Retnowati (STKIP Singkawang, 2018)
The research objectives are to determine the effect of Organizational Culture and Decision making toward organizational citizenship behavior of teacher in pre-school. The research was conducted sampling to 175 respondent teacher of pre-school at Bogor City with Path Analysis design. The results are; (1) Organizational Culture has direct influence toward Organizational Citizenship Behavior of teacher in pre-school (2) Decision making has direct influence toward Organizational Citizenship Behavior of teacher in pre-school (3) Organizational Culture has direct influence toward Decision making. Conclusion, in enhancing organizational citizenship behavior of teacher in pre-school would be strengthening on Organizational Culture and Decision making.